Design and evaluation of an ironless stator axial flux permanent magnet machine - Lombard, Nicolas F.(Nicolas Frederick) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1997.